JENIS-JENIS BASIDIOMYCOTA DI KAWASAN AIR TERJUN CURUG PANDAN KABUPATEN LAHAT SERTA SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI DI SMA (BASIDIOMYCOTA TYPES IN THE WATERFALL CURUG PANDAN LAHAT AND CONTRIBUTION TO HIGH SCHOOL BIOLOGY LEARNING) - Putri Hera Mayang Sari; Khoiron Nazip; Endang Dayat (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2016)
Abstract: Research on Types of Basidiomycota in waterfall Curug Pandan Lahat was conducted from February to March 2015. The purpose of this study was obtained information on the types Basidiomycota found in this region. The method used is descriptive. Sampling was done by means of exploration. The focus of this research is only at the macroscopic Basidiomycota. Collection observed Basidiomycota were identified based on morphological characteristics. Results of the study identified 20 types Basidiomycota included into the 5 orders and 10 Families. The type most commonly found was of the Orders Agaricales which disseminatus Coprinus (Pers.: Fries) JE Lange., Mycena chlorophos, Mycena rosella (Fr.) P. Kumm., Favolaschia calocera, Marasmius androsaceus (L.) Fr., Micromphale foetidum , Cyptotrama asprata, Psathryrella, and Schizophyllum commune var. Multifidium. Polyporales Orders that is Cymatoderma elegans Var Lamellatum, Lenzites elegans (Spreng.) Pat., Lentinus sajor-caju (Fr.) Fr., Earliella scabrosa (Pers.) Gilb. & Ryvarden, Trametes elegans, Pycnoporus sanguineus. (L.) Murrill, Lenzites sp, and Microporus xanthopus (Fr) Kuntze. Cantharellales Orders consists of Clavulina cinerea (Bull.) J. Schrot. Orders of Thelephorales consists of Thelephora vialis Schwein. Nation of Russulales consists of Stereum Ostrea. Information from this study contributed to instructional materials in Biology in high school learning basic competencies 2.4 Describe the characteristics and types of fungi based on observations, experiments, and review of the literature as well as its role for life. Keywords: Basidiomycota, Waterfall Curug Pandan, Lahat